2016
DOI: 10.1155/2016/3058393
|View full text |Cite|
|
Sign up to set email alerts
|

Inositols in the Treatment of Insulin-Mediated Diseases

Abstract: A growing body of research is currently focused on the role of inositol isomers and in particular myo-inositol (MYO-INS) and D-chiroinositol (DCI) in the treatment of insulin resistance states. Both isomers have been shown to exert insulin-mimetic action and to lower postprandial glucose. Further, insulin resistance-related diseases were associated to derangements in inositol metabolism. Thus, the aim of this review is to provide current evidence on the potential benefits of inositol isomers (MYO-INS and DCI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 50 publications
2
33
0
1
Order By: Relevance
“…16 It has been observed that Curcumin, in a highly water dispersible formulation, improves glucose tolerance by stimulating the secretion of incretin glucagon-like peptide 1 (GLP-1). 17 Regarding inositol, it has been shown that some isomers, myo-inositol and D-chiro-inositol, perform the function of second messengers of insulin: 18 clinical studies have shown that taking these compounds improves insulin resistance and reduces cardiovascular risk factors in women with polycystic ovary syndrome, 19,20 gestational diabetes mellitus 21,22 and metabolic syndrome postmenopause. 23,24 The aim of this study was to evaluate the effects of a nutraceutical containing Berberine, Curcumin, Inositol, Banaba, and Chromium Picolinate (Reglicem ® ) on the regression of the impaired fasting glucose (IFG) or IGT condition in patients with dysglycemia and on the glycolipid metabolism in patients with IFG or IGT status.…”
Section: Introductionmentioning
confidence: 99%
“…16 It has been observed that Curcumin, in a highly water dispersible formulation, improves glucose tolerance by stimulating the secretion of incretin glucagon-like peptide 1 (GLP-1). 17 Regarding inositol, it has been shown that some isomers, myo-inositol and D-chiro-inositol, perform the function of second messengers of insulin: 18 clinical studies have shown that taking these compounds improves insulin resistance and reduces cardiovascular risk factors in women with polycystic ovary syndrome, 19,20 gestational diabetes mellitus 21,22 and metabolic syndrome postmenopause. 23,24 The aim of this study was to evaluate the effects of a nutraceutical containing Berberine, Curcumin, Inositol, Banaba, and Chromium Picolinate (Reglicem ® ) on the regression of the impaired fasting glucose (IFG) or IGT condition in patients with dysglycemia and on the glycolipid metabolism in patients with IFG or IGT status.…”
Section: Introductionmentioning
confidence: 99%
“…In the article titled “Inositols in the Treatment of Insulin-Mediated Diseases” [1], the fifth affiliation was incorrectly written as “Fertility Techniques SSD, “S. Giovanni di Dio e Ruggi d'Aragona” University Hospital, CMSO (Centro Medico Specialistico Orio), 84131 Salerno, Italy.” The affiliation “CMSO (Centro Medico Specialistico Orio), 84127 Salerno, Italy” should have been added as a separate affiliation.…”
mentioning
confidence: 99%
“…DCI therefore acts as an insulin-sensitizing agent, and has shown promise as a treatment for diseases with glucose intolerance, such as polycystic ovarian syndrome (PCOS) and T2DM [8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Myo-inositol (MYO-INS) and D-chiro-inositol (DCI) are stereoisomers of inositol which have been shown to exert insulinmimetic action and to lower postprandial glucose. In particular, DCI plays a key role in the insulin pathway, acting as insulin sensitizing through the enhancement of glucose peripheral tissue uptake and glycogen synthesis [7][8][9][10][11]. Thanks to these effects, they have been used for the treatment of insulin resistance states as polycystic ovary syndrome (PCOS), T2DM or GDM [12,13].…”
Section: Introductionmentioning
confidence: 99%